2018
DOI: 10.4269/ajtmh.18-0395
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Case–Control Study to Evaluate the Diagnostic Accuracy of Honeycomb Sign in Melioid Liver Abscess

Abstract: Among pyogenic liver abscesses, melioid etiology is considered in endemic regions in the presence of known health or occupational risk factors. "Honeycomb sign," used to describe an abscess with multiple internal septations dividing the abscess cavity into multiple loculations of comparable sizes on imaging, is a sensitive sign for melioid liver abscess. This is a retrospective case-control study investigating incidence, sensitivity, and specificity of "honeycomb sign" in melioid liver abscess, in a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…A retrospective study in patients with culture-proven melioidosis in India demonstrated that 23/189 (12%) had liver abscesses, a similar proportion to the 11% in our study. 11 In Thailand, a prospective observational study in 230 patients with culture-confirmed melioidosis found one or more abscesses in the liver and/or spleen in 77 (33%) patients, 12 similar to the 28% observed in our study. Other studies have demonstrated that the combination of liver and splenic abscesses can be predictive for melioidosis.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…A retrospective study in patients with culture-proven melioidosis in India demonstrated that 23/189 (12%) had liver abscesses, a similar proportion to the 11% in our study. 11 In Thailand, a prospective observational study in 230 patients with culture-confirmed melioidosis found one or more abscesses in the liver and/or spleen in 77 (33%) patients, 12 similar to the 28% observed in our study. Other studies have demonstrated that the combination of liver and splenic abscesses can be predictive for melioidosis.…”
supporting
confidence: 86%
“…Finally, we used a low-cost ultrasound machine, which may have limited the detection of very small abscesses as well as the morphological characteristics suggestive of melioidosis (such as the "necklace" or "honeycomb" appearance previously described in melioidosis). 11 Nevertheless, we intentionally opted for using simple equipment and simple image characteristics, as these more realistically reflect the conditions under which POCUS is applied. Furthermore, by adding a linear probe for screening of the spleen and soft tissue, we allowed for more sensitive detection of small abscess.…”
mentioning
confidence: 99%
“…Melioid abscesses in the liver could be larger or smaller. Honeycomb sign is found to be specific for melioidosis [38]. Abscesses in the liver and spleen are not commonly encountered in tuberculosis, whereas they are common with other pyogenic infections.…”
Section: Discussionmentioning
confidence: 99%
“…For prostatic abscesses, ultrasound has a sensitivity of approximately 85%, compared with 99% by CT (472). With regard to liver abscesses, the CT scan "honeycomb sign," described as an abscess with multiple similar-size loculations separated by thin septa, has a sensitivity of 85%, a tion of melioidosis visceral abscesses appears to favor CT scan (472,494). However, in resource-limited settings, ultrasound evaluation of all bacteremic melioidosis cases may be warranted.…”
Section: Imagingmentioning
confidence: 99%